ALS model-based comparison of Cosmo-SkyMed and TerraSAR-X HS DSMs on varied land forms. Issue 1 (2nd January 2016) - Sefercik, Umut G.; Yastikli, Naci
Abstract : Since 2007, the revolutionary X-band synthetic aperture radar (SAR) satellites Cosmo-SkyMed (CSK) and TerraSAR-X (TSX) have been collecting high-resolution images that are convenient for digital surface model (DSM) acquisition by the interferometric SAR (InSAR) technique. In this study, the potential of DSMs derived from CSK and TSX high-resolution spotlight (HS) images is thoroughly analysed regarding the basic accuracy metrics absolute vertical accuracy (AVA) and relative vertical accuracy (RVA). Utilising convenient InSAR pairs, 2 m gridded DSMs are generated in Istanbul and validated with model-based comparisons using an actual airborne laser scanning (ALS) DSM. Results show that CSK and TSX DSMs are compatible in open, built-up and forest land forms. The AVAs are between 8 m and 10 m based on standard deviation of height discrepancies against the ALS model. The RVAs, calculated by the coherence of neighbouring pixels for each DSM, are superior to AVAs for both CSK and TSX.